PHS5 Integrated mobile phone application to support the three pillar of end tuberculosis strategy : a new approach before 2030 - Gilbert Renardi Kusila (Fakultas Kedokteran Universitas Gadjah Mada, 2019)
Background : Indonesia as the highest number of tuberculosis (TB) cases is burdened by both classic unsolved problem and latest issues of TB cases. Innovation using mobile phone application may be potential to integrate several TB control efforts to reach the tuberculosis-free target in year 2030Aim : to review the benefit and applicability of mobile phone application to support the three pillar of end TB strategy, especially in Indonesia.Method : This is a narrative literature review study. Extracting the component and occured problems from each pillar of end TB strategy was firstly conducted. For each findings, the approachment using mHealth were searched in published papers, pilot tested, and GO/NGOs or company website to be reviewed whether it could be performed and applied as one stop integrated mobile application that suitable for Indonesian population.Result : mobile phone and internet penetration in Indonesia is fast increasing, predominantly among lower class society. Separated and various applications found to deal with health services related problems, those could also be implemented to overcome TB based on three pillar strategy in one integrated application. Government played a big role to promote investation, wide use of the application, and creating a connected platform where different type of health startup can enter to support the system. More suggestions are needed on how this integrated application should deal with the ethical clearance to use the big data for medical research, users’ age, rural area implementation, and economic gap.Conclusion : “One stop” concept in one integrated application will enhance the will of wide population to use it and the sustainability of the application. To maximize its benefit to overcome TB in Indonesia, gross participation from individual, community, private sector, until the national government level should be endeavored.